Pediatric Gastrointestinal Posttransplant Lymphoproliferative Disorder: Incidence, Clinical Characteristics, and Impact of Major Surgical Interventions Upon Overall Survival. Issue 6 (August 2018) - Dziegielewski, Claudia; Contreras, Rodrigo; Weitzman, Sheila; Gerstle, Justin T.
Abstract : Posttransplant lymphoproliferative disorder (PTLD) is a severe complication of solid organ transplantation. A common site for PTLD development is the gastrointestinal (GI) tract. The purpose of this study was to evaluate the incidence, clinical features, and overall survival of pediatric patients with GI-PTLD, and to assess whether major surgical interventions increased mortality. Records of pediatric transplant patients who developed GI-PTLD between January 2000 and June 2015 were retrospectively reviewed at our institution. Of 814 patients who received solid organ transplants, 34 (4%) developed GI-PTLD. Lung and multiorgan transplants had the highest incidence of GI-PTLD (both 11%). Patients often had multisite GI involvement (47%). Within the first year of transplantation, 38% of the 34 patients developed GI-PTLD. Of the patients with Epstein-Barr Virus–positive disease, 12/22 (55%) presented in the first 12 months of transplantation, compared with only 1/12 (8%) of the patients with Epstein-Barr Virus–negative disease ( P =0.002). Major surgical interventions were required in 41% of patients; overall survival rate for these surgical patients was 71%, compared with 60% for patients not requiring major surgical interventions ( P =0.49). Despite multimodal treatments, overall survival remains poor for patients with GI-PTLD; however, major surgical intervention did not significantly impact overall survival in this cohort.